Validation of the clinical utility of sGaw as a response variable in methacholine challenge testing. Issue 5 (7th December 2022) - Parker, Jacqueline; Tzeng, Allison; Wayne, Shawn; Haynes, Jeffrey M.; Irvin, Charles G.; Kaminsky, David A.
Abstract: Background and Objective: Airway hyperresponsiveness (AHR) is commonly assessed by a methacholine challenge test (MCT), during which a provocative concentration causing a 20% reduction in forced expiratory volume in 1 second (FEV1 ) (PC20 ) < 8 mg/ml is considered a positive response. However, a fall in specific airway conductance (sGaw) may also have clinical significance. The purpose of this study was to assess whether AHR determined by a provocative concentration causing a 40% reduction in sGaw (PC40 ) < 8 mg/ml corresponds to a clinical diagnosis of asthma. Methods: We analysed the changes in spirometry, lung volumes and sGaw during MCT in 211 randomly selected patients being evaluated for AHR to support a clinical diagnosis of asthma. Results: The mean (SD) age of the group was 53 (15) years, with 141 women (67%). Overall lung function was normal, with FEV1  = 92 (15) % predicted, total lung capacity = 97 (13) % predicted and sGaw = 0.19 (0.15–0.23) L/s/cm H2 O/L, (median, 25–75 IQR). There were many more patients who responded by PC40 only ( n  = 120) than who responded by PC20 ( n  = 52). There was no significant difference in asthma diagnosis between the PC20 (98%) and PC40 (93%) groups, and we estimate 34% of patients with a diagnosis of asthma would have been classified as having no AHR if only the FEV1 criterion was used. Conclusion: Changes in sGaw during MCT indicate clinically significant AHR in support of a clinical diagnosis of asthma among patients being evaluated for asthma. Abstract : Airway hyperresponsiveness may be reliably diagnosed by changes in specific airway conductance alone during methacholine challenge. Up to 34% of patients with clinically confirmed asthma would have been classified as having no airway hyperresponsiveness if only changes in FEV1 were used. See related Editorial